2016
DOI: 10.3390/met6030043
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Tensile Properties of Precipitation-Hardened Al-Mg-Cu-Si Alloys

Abstract: Abstract:Because the mechanical performance of precipitation-hardened alloys can be significantly altered with temperature changes, understanding and predicting the effects of temperatures on various mechanical properties for these alloys are important. In the present work, an analytical model has been developed to predict the elastic modulus, the yield stress, the failure stress, and the failure strain taking into consideration the effect of temperatures for precipitation-hardenable Al-Mg-Cu-Si Alloys (Al-A31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…This indicates that the strength of the alloys significantly increases while their elongation decreases when the Cu content increases to 2.5%. Besides, in our study, it shows that either the Cu content or the aging treatment has little influence on the elastic modulus of aluminium alloy, which is in accordance with the results of previous studies [6,7]. Figure 10a shows the tensile curves of the four as-quenched alloys.…”
Section: Age-hardening Curvessupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that the strength of the alloys significantly increases while their elongation decreases when the Cu content increases to 2.5%. Besides, in our study, it shows that either the Cu content or the aging treatment has little influence on the elastic modulus of aluminium alloy, which is in accordance with the results of previous studies [6,7]. Figure 10a shows the tensile curves of the four as-quenched alloys.…”
Section: Age-hardening Curvessupporting
confidence: 92%
“…Esmaeili et al [20] found that both β" and Q precipitates occurred in the peak-aged alloy, but only the β" precipitate was the main cause of age-hardening. Wang et al [18], and Lu et al [14], support Esmaeili et al Miao et al [21], and Saito et al [7] stated that the Q precipitates were mostly formed in over-aged conditions rather than peak-aged conditions: However, some other studies find that both β" and Q precipitates contributed to the strength increase of the alloy. Moreover, Jin et al [5] and Farkoosh et al [10] found that the Q precipitate plays the major role in improving the age-hardening of alloys with Cu addition.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The high-temperature mechanical behavior of Al-Si-based casting alloys has mainly been investigated for piston alloys [5,6], of nearly eutectic or hypereutectic composition. Only recently has attention been focused on hypoeutectic alloys [7,8]. As a matter of fact, during their lifecycle, structural parts made of these alloys are held at moderate or high temperatures (for example in parts close to heat sources where the high thermal conductivity of Al alloys is appreciated) and the knowledge of high-temperature tensile properties in their actual temper condition is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, during their lifecycle, structural parts made of these alloys are held at moderate or high temperatures (for example in parts close to heat sources where the high thermal conductivity of Al alloys is appreciated) and the knowledge of high-temperature tensile properties in their actual temper condition is of interest. While many experimental studies have been devoted to the thermal stability of Al-Si-Cu casting alloys and to their direct effects on hardness and room-temperature mechanical properties [7,8], less attention has been paid to the temperature dependence of stress-strain curves and the tensile properties in a wide temperature range [8]. Small efforts have also been dedicated to describe the effects of microstructural stability on the mechanical properties after long-term exposure to elevated temperatures, for instance by means of long-term experimental creep tests [9] or tensile testing in a wide range of strain rates [8].…”
Section: Introductionmentioning
confidence: 99%